Long-stay tourists: Developing a theory of intercultural integration into the destination neighbourhood. (October 2019) - Anantamongkolkul, Chidchanok; Butcher, Ken; Wang, Ying
Abstract: This study is the first to investigate intercultural behavioural patterns of long-stay tourists in a culturally unfamiliar leisure holiday destination. Information was collected on-site from forty-four tourists from Europe, the U.S and Australia visiting an internationally popular beach destination in Thailand. A novel approach to data collection involved one-to-one interviews triangulated with a set of dyadic interviews to better understand shared travel experiences. Onsite travel behaviour reflected neighbourhood activities rather than tourist behaviour. Four distinct levels of intercultural adaptation strategies were categorised, ranging from staying in a home comfort zone to adopting the destination as a second home. Classic transaction based marketing strategies for long-stay tourists are inadequate and more attention is needed on destination hospitableness and relationship building. Highlights: The first to investigate intercultural behavioural patterns of long stay tourists in culturally unfamiliar destination. Data collection involving one-to-one interviews triangulated with a set of dyadic interviews. Suggesting on-site travel behaviour reflected neighbourhood activities rather than tourist behaviour. Identifying four distinct levels of intercultural adaptation strategies. Requiring a shift from transaction based marketing to destination hospitableness and relationship building.